Analysis of shoulder dystocia management and development of learning media to improve midwifery competency - Fariesa Dinda Aurelia; Rini Gustina Sari; Winda Aprilia (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Shoulder dystocia is a potentially life-threatening obstetric complication for the mother and neonate, but its management is often suboptimal due to limited competence of midwifery personnel in emergency situations. Purpose: to analyze the management patterns of shoulder dystocia based on a systematic literature review and evaluate the effectiveness of developing 3D animated video-based learning media using the ADDIE model in improving midwifery competency. Method: A quantitative approach with a systematic literature study design was used, sourced from five selected scientific journals containing case data, clinical interventions, and development of midwifery learning media. Results: The analysis results showed that the McRoberts maneuver was the primary management technique with a success rate of 42–58%, followed by suprapubic pressure (34-42%) as an additional intervention. The incidence of shoulder dystocia was recorded to be higher in deliveries with a history of macrosomia, gestational diabetes, and vaginal delivery in primigravida adolescents. The implementation of 3D animated video-based learning media using the ADDIE model has been shown to significantly improve midwifery students' competency scores (p < 0.001), with an average increase of 23.4 points from pretest to posttest. Conclusion: The novelty of this study lies in the integration of clinical analysis of shoulder dystocia with a standardized learning media development strategy, a practice never before comprehensively implemented in the context of midwifery education in Indonesia. The implications of this study are relevant for developing a competency-based curriculum and improving the preparedness of midwifery personnel in facing obstetric emergencies.